2006
DOI: 10.1016/j.learninstruc.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Process support in learning tasks for acquiring complex cognitive skills in the domain of law

Abstract: Whole tasks for acquiring complex skills are often too difficult for novices. To solve this problem, process support divides the problem solving into phases, offers driving questions, and provides feedback. A multimedia program was used to teach sophomore law students (N ¼ 82) to prepare and carry out a plea. In a randomised 2 Â 2 design with the factors number of phases and availability of driving questions, students solving a task with fewer phases performed better and more efficiently than students exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In addition, there were a number of researchers who investigated how to increase the germane cognitive load (Gerjets et al 2006;Nadolski et al 2006;Paas and van Merri/nboer 1994;van Gog et al 2006). However, worked examples were not effective in all those cases.…”
Section: Worked Examples and Prior Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were a number of researchers who investigated how to increase the germane cognitive load (Gerjets et al 2006;Nadolski et al 2006;Paas and van Merri/nboer 1994;van Gog et al 2006). However, worked examples were not effective in all those cases.…”
Section: Worked Examples and Prior Knowledgementioning
confidence: 99%
“…Recently, there have been rapid developments in the use of computer-based learning environments related to worked examples (Gerjets et al 2006;Gerjets et al 2008;Jung and Kim 2006;Kalyuga et al 2001;Kim 2005;Nadolski et al 2006;Paas and van Merri/nboer 1994;Schworm and Renkel 2006;van Gog et al 2006van Gog et al , 2008 (Crippen and Earl 2007;Gerjets et al 2008;Gerjets et al 2006;Kim 2005;Paas and van Merri/nboer 1994;Schworm and Renkel 2006). Moreover, Crippen and Earl (2007), Gerjets et al (2006), and Schworm and Renkel (2006) explored whether the prompts of self-explanations or instructional explanations in the worked example instructions enhanced the performance.…”
Section: Worked Examples In the Computer-based Learning Environmentsmentioning
confidence: 99%
“…See also [10,11]. A process worksheet provides a generic, but content-based, description of the phases one should go through when solving a problem.…”
Section: Introductionmentioning
confidence: 99%
“…They guide students to accomplish the key phases of the whole task, help learners to activate prior knowledge and offer relevant resources to solve tasks efficiently. IPS research shows that driving questions turn out to be a useful supporting tool for assisting students through the phases and skills required to solve IPS tasks [35,36]. In this line, [23] found that driving questions had positive effects in regulating the IPS process in higher education.…”
mentioning
confidence: 97%
“…In this line, [23] found that driving questions had positive effects in regulating the IPS process in higher education. The authors of [36] also used driving questions to aid law students in the proper use of electronic resources and guide them through their learning process.…”
mentioning
confidence: 99%